La psicología de la nueva era: Ensayo sobre la cultura religiosa postmoderna - Sánchez López, Saúl (Nómadas. Critical Journal of Social and Juridical Science, 2015)
The main characteristic of postmodern religious culture is that faith has become permeable to personal will and viewpoints. In the background, there is a certain psychology constituted by an eclectic episteme, a relativistic hermeneutics and a hedonist ethos, so that an individualized recreation of religion takes place, depending on a free choice, reinterpretation and mix of elements according to what seems more convincing and satisfactory. This psychology is best exemplified by the New Age current, but it is also present in other postmodern religious cultural phenomena such as the new religious movements, progressive Christian organizations and even social discourses concerning religious tolerance. Because of its nihilistic nature, this new age psychology encourage the de-essentialization of religion, eroding its conventional form: institutional, doctrinal and normative, opening instead a new way of spiritual development, corresponding to the individual consciousness and common will.